THE EFFECTS OF CAR INSURANCE CUSTOMER PERCEPTION TOWARD PUBLIC RELATION AND CUSTOMER LOYALTY - JOHANNES SIMATUPANG; HARRY BUDY (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The purpose of this research is to explain the effect of customer perception on PublicRelationtoward brandimage and to customer loyalty. Research used surveywhere carinsurace customer is the population. Research result showed that range score of public relation perception, brand image, and customer loyalty have good value. According to SEM analysis result shows that the higher the customerpersceptionon public relation causes the higher the brand image. and the higher the brand image causes higher customer loyalty. So, public relation has positive effect to brand image and customer loyalty. Hence, public relation as a marketing tool should be developed internally to craft the more comprehensive marketing strategy to make customer be loyal and winning the competitions.